1992
DOI: 10.1111/j.1432-1033.1992.tb16990.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of phospholipase C by guanine‐nucleotide‐binding protein βγ subunits

Abstract: We have previously shown that soluble fractions obtained from human HL-60 granulocytes contain a phospholipase C which is markedly stimulated by the stable GTP analogue guanosine 5'-[3-O-thio]triphosphate (Camps, M., Hou, C., Jakobs, K. H. and Gierschik, P. (1990) Biochem. J. 271, 743 -7481. To investigate whether this stimulation was due to a soluble c1 subunit of a heterotrimeric guanine-nucleotide-binding protein or a soluble low-molecular-mass GTP-binding protein, we have examined the effect of purified gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 270 publications
(116 citation statements)
references
References 96 publications
7
108
1
Order By: Relevance
“…The diffusion of ␤ 1 ␥ 2 -stimulated PLC␤ 2 (or PLC␤ 2 ⌬) is also much faster than that of PtdInsP 2 , which has D values of 0.5-1 m 2 /s (32, 34), enabling very fast spatial dispersal of the activated enzyme, not limited by the lateral diffusion of either lipidated protein targets or the substrate. This mechanism is likely relevant under physiological conditions, because PLC␤s are typically much less abundant (at least 100-fold) in cells than ␤␥ dimers (64,65), enabling sequential interaction of a single PLC␤ molecule with multiple ␤␥ dimers by dissociation and fast re-association. An important consequence of this fast diffusion is a dramatic increase in the travel range of ␤ 1 ␥ 2 -activated PLC␤ 2 (or PLC␤ 2 ⌬) to at least 1.9 m. This implies that stimulation by ␤ 1 ␥ 2 recruits PLC␤ 2 to act on dispersed PtdInsP 2 populations.…”
Section: Discussionmentioning
confidence: 99%
“…The diffusion of ␤ 1 ␥ 2 -stimulated PLC␤ 2 (or PLC␤ 2 ⌬) is also much faster than that of PtdInsP 2 , which has D values of 0.5-1 m 2 /s (32, 34), enabling very fast spatial dispersal of the activated enzyme, not limited by the lateral diffusion of either lipidated protein targets or the substrate. This mechanism is likely relevant under physiological conditions, because PLC␤s are typically much less abundant (at least 100-fold) in cells than ␤␥ dimers (64,65), enabling sequential interaction of a single PLC␤ molecule with multiple ␤␥ dimers by dissociation and fast re-association. An important consequence of this fast diffusion is a dramatic increase in the travel range of ␤ 1 ␥ 2 -activated PLC␤ 2 (or PLC␤ 2 ⌬) to at least 1.9 m. This implies that stimulation by ␤ 1 ␥ 2 recruits PLC␤ 2 to act on dispersed PtdInsP 2 populations.…”
Section: Discussionmentioning
confidence: 99%
“…The overall LDCL produced was only 5 -15 % lower than in the presence of 50 pM A13+, whereas the kinetics of the responses did not change (data not shown). On the other hand, it was reported that G,, subunits of pertussis-toxin-sensitive or insensitive Gproteins stimulated directly phospholipase C of bovine liver cytosol [39], of HL60 cytosol and membrane, of human and bovine peripheral neutrophils [40] or turkey erythrocytes [41]. Recently it has been shown that AlF,-is a potent activator of heterotrimeric G-proteins (G,,, GJ but has no action at all on low-molecular-mass G-proteins (p21 Ha-ra\, rap, rab and arf subfamilies) [42].…”
Section: Discussionmentioning
confidence: 99%
“…cyclase [4]~ facilitate the stimulation of type I1 and type IV adenylyl cyclase by activated ~x~ [4], regulate an unidentified effector moiety involved in the yeast pheromone response [8], and stimulate phospholipase C [9].…”
Section: Introductionmentioning
confidence: 99%